Green jobs in the Brazilian Pantanal region (Sustainability in Debate, 2017)
The Pantanal wetlands region, considered as a world natural heritage and biosphere reserve by UNESCO, has simultaneously, activities that can protect and attack the environment. In this context, the concern to develop these activities in balance with the environment has been a constant concern for the region. One of the tools for this to happen is the use of the green economy. In this article, we measure green jobs in the Pantanal region between the years 2002 and 2015, based on data from the RAIS of the Ministry of Labor. We identified that the number of green jobs in the Pantanal region has declined between 2002 and 2015. However, there is hope for improvement as the number of jobs tending to protect the environment grew over the same period.